Atomistic picture of electronic metal support interaction and the role of water - Fusek, Lukáš; Farnesi Camellone, Matteo; Ronovský, Michal; Kastenmeier, Maximilian; Skála, Tomáš; Kumar Samal, Pankaj; Tsud, Nataliya; Mehl, Sascha; Škvára, Jan; Dolák, Tomáš; Uvarov, Vitalii; Setvín, Martin; et al. (Journal of Materials Chemistry A, 2024)
Single atom catalysis (SAC) represents an emerging area of heterogeneous catalysis but faces challenges related to the low density of active sites and poor thermal stability. In this work, we present new fundamental insights into the nature of electronic metal support interactions (EMSI) coupled with cation exchange, which yield high density of atomically dispersed noble metals on defect-free terraces of cation-terminated reducible oxides. On well-ordered Co3O4(111) films, the mechanism involves temperature-controlled substitution of surface Co2+ and sub-surface Co3+ cations by Pt2+ and Pt4+ species, respectively. The cation exchange with Co2+ is coupled with the partial reduction of Co3O4(111), while the cation exchange with Co3+ involves the charge disproportionation within the Pt species. In the presence of co-adsorbed water, the Pt4+ species are stabilized at the surface in the form of triaqua complexes.
CRIS-Team Scopus Importer:2024-02-09